2016
DOI: 10.1186/s12889-016-3253-0
|View full text |Cite
|
Sign up to set email alerts
|

Does retirement mean more physical activity? A longitudinal study

Abstract: BackgroundEvidence on physical activity (PA) and transitions out of full-time employment in middle-to-older age is mainly cross-sectional and focused upon retirement. The purpose was to examine trajectories in PA before and after transitions out of full-time employment.MethodsData were obtained for 5,754 people in full-time employment aged 50–75 from the US Health and Retirement Survey. Logistic regression was used to examine trajectories in twice-weekly participation in light, moderate and vigorous PA among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…With regard to the type of retirement, findings were heterogeneous. Transitioning to fulltime and voluntary retirement was linked to increased PA levels [89,90], whereas transitioning to economic inactivity due to disability led to decreases [89,105]. For the latter, however, one study reported declines in women only, whereas men increased their PA [96].…”
Section: Employment-related Events and Transitionsmentioning
confidence: 99%
“…With regard to the type of retirement, findings were heterogeneous. Transitioning to fulltime and voluntary retirement was linked to increased PA levels [89,90], whereas transitioning to economic inactivity due to disability led to decreases [89,105]. For the latter, however, one study reported declines in women only, whereas men increased their PA [96].…”
Section: Employment-related Events and Transitionsmentioning
confidence: 99%
“…reported that the amount of exercise and leisure-time physical activity increases after the retirement transition19. Similarly, a recent longitudinal study has confirmed this and observed that the amount and intensity of physical activity could change by the type of transition out of full-time employment among middle-aged and older adults20. All participants enrolled in this study were retired workers, who have no occupational physical activity and may spend more time on regular non-occupational physical activity, gaining more mortality benefits from physical activity than those in other studies.…”
Section: Discussionmentioning
confidence: 67%
“…A systematic review identified 19 articles published through July 2010 [19]. Thirteen additional articles were published since this review [22,32,36,70,[83][84][85][86][87][88][89][90][91] (Table 2). Most of these 32 articles evaluated self-reported leisure-time physical activity among adults who retired during follow-up compared to those who continued working.…”
Section: Physical Activity During the Retirement Transitionmentioning
confidence: 99%
“…Existing studies often used single-item summary measures of physical activity and excluded occupational physical activity, which has contributed to discrepant findings across studies. In addition, behavior change at retirement may vary by socioeconomic position (SEP) because disadvantaged adults are more likely to retire due to ill health or job loss rather than voluntarily [20][21][22].…”
mentioning
confidence: 99%